PENGGUNAAN MODEL PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN MENARIK KESIMPULAN SEBUAH TEKS BACAAN - Nurmitasari Nurmitasari; Merlinda Atika Sari; Merita Sari; Miftahul Khasanah; Oktaviani Oktaviani; Putri Aulia Rahma (LPPM Universitas Cipta Mandiri, 2026)
This study aims to determine the effect of the Think Talk Write (TTW) learning model on students' ability to draw conclusions from a reading text in the Indonesian language subject for grade V at the UPT SD Negeri 1 Pringsewu Utara. The study used a quantitative approach with a Pre-Experimental One Group Pretest–Posttest Design. The subjects were all 20 grade V students. The research instrument was a multiple-choice test consisting of 15 questions that had been tested for validity and reliability using the Point Biserial and KR-20 techniques. Data analysis included a normality test with Lilliefors, a homogeneity test with the F test, and a paired sample t-test. The results showed that the data were normally distributed and homogeneous, with a value of thitung = 22.7225 and ttabel = 2.04523 at a significance level of 0.05. Since thitung > ttabel, H₀ is rejected and Hₐ is accepted. Thus, there is a significant difference between student learning outcomes before and after the implementation of the TTW model. This shows that the Think Talk Write learning model is effective in improving students' ability to draw conclusions from reading texts.